First Dual Responsive "Turn‐On" and "Ratiometric" AIEgen Probe for Selective Detection of Hydrazine Both in Solution and the Vapour Phase1. Issue 18 (4th March 2019) - Purohit, Deepak; Sharma, Chandra P.; Raghuvanshi, Ashutosh; Jain, Ankita; Rawat, Kundan S.; Gupta, Neeraj M.; Singh, Jagriti; Sachdev, Monika; Goel, Atul
Abstract: A new dual responsive "turn‐on" and "ratiometric" aggregation‐induced emission luminogen (AIEgen) 3‐formyl‐5‐(piperidin‐1‐yl)biphenyl‐4‐carbonitrile6 a (FPBC6 a ) for selective detection of hydrazine in solution as well as in vapour phase is described. At a low concentration of 2.5 μm, the probe FPBC6 a is non‐fluorescent (turn‐off) but remarkably lights up (turn‐on with blue emission) in the presence of hydrazine solution (0.25–25 μm ). Interestingly, at higher concentrations, the nanoaggregates of FPBC6 a (>25 μm, 99 % HEPES in DMSO) displayed ratiometric response in the presence of hydrazine with a remarkable hypsochromic shift from the green (500–550 nm) to blue regions (440–480 nm). Furthermore, a real application of FPBC6 a was successfully demonstrated through the detection and visualization of hydrazine in live cervical cancer cells as well as using portable test strips. Abstract : Got any rocket fuel? A new dual‐acting "turn‐on" and "ratiometric" aggregation‐induced emission luminogen (AIEgen) 3‐formyl‐5‐(piperidin‐1‐yl)biphenyl‐4‐carbonitrile6 a for selective detection of hydrazine in solution as well as in the vapour phase is described.